The Traceability of Physical Education under the Vision of Life Education - Zhang, Jinghan (International Journal of Social Sciences and Public Administration, 2024)
The value of this study is to discuss the feasibility of physical education under the vision of life education by combining the life education in physical education. The author thinks that the life education in physical education can be classified into three aspects: (1) natural life perfect education (survival education, physical health education, mental health education). (2) social life adaptation and development education.(3) spiritual life promotion education. Physical education should be carried out by combining the three aspects covered by the above life education, so as to enhance the height of physical education and the quality of physical education.